Visceral leishmaniasis in Brazil: rationale and concerns related to reservoir control - Werneck, Guilherme Loureiro (Revista de Saúde Pública, 2014)
The control of zoonotic visceral leishmaniasis is a challenge, particularly in Brazil, where the disease has been gradually spreading across the country over the past 30 years. Strategies employed for decreasing the transmission risk are based on the control of vector populations and reservoirs; since humans are considered unnecessary for the maintenance of transmission. Among the adopted strategies in Brazil, the sacrifice of infected dogs is commonly performed and has been the most controversial measure. In the present study, we provide the rationale for the implementation of different control strategies targeted at reservoir populations and highlight the limitations and concerns associated with each of these strategies.